Comparison of new and 3-month-old brush heads in the removal of plaque using a powered toothbrush - Louise M. E. Hogan (Blackwell Synergy, 2007)
Aim: To compare the effectiveness of new and 3-month-old worn brush heads in plaque removal using a rotation–oscillation-powered toothbrush. Material and Methods: A single examiner blinded, randomized, cross-over study was conducted in which 34 adults attended the clinic on two occasions following 48-h periods of no oral hygiene. Following plaque scoring, subjects brushed for 2 min. with either a new brush or a brush they had used for 3 months and plaque was then rescored. Bristle wear was assessed by measuring brushing surface areas on digital images. Results: The mean plaque score percentage reductions with new brush heads were not significantly different from those achieved with 3-month-old heads for total surfaces (new538.1%; worn537.1%; p50.83) and approximal surfaces (new531.3%; worn530.8%; p50.9). Brushing surface area increases of the 3-month-old heads ranged from 0% to 135% (mean 26.9%). Compared with new brush heads, no significant differences were found for plaque score reductions for heads with minor, moderate or marked wear. Conclusion: Rotation–oscillation-powered toothbrushes with 3-month-old brush heads exhibiting various degrees of wear were as effective as new brush heads in plaque removal. Bristle age and wear on a powered toothbrush may not impede the effectiveness of plaque removal.